Evaluation of marginal fit of two allceramic copings with two finish lines - Subasi, Gulce; Ozturk, Nilgun; Ozgur, Inan; Bozogullari, Nalan (European Journal of Dentistry, 2012)
Objectives: This in-vitro study investigated the marginal fit of two all-ceramic copings with 2 finish line designsMethods: Forty machined stainless steel molar die models with two different margin designs (chamfer and rounded shoulder) were prepared. A total of 40 standardized copings were fabricated and divided into 4 groups (n=10 for each finish line-coping material). Coping materials tested were IPS e.max Press and Zirkonzahn; luting agent was Variolink II. Marginal fit was evaluated after cementation with a stereomicroscope (Leica MZ16). Two-way analysis of variance and Tukey-HSD test were performed to assess the influence of each finish line design and ceramic type on the marginal fit of 2 all-ceramic copings (α =.05) Results: Two-way analysis of variance revealed no statistically significant differences for marginal fit relative to finish lines (P=.362) and ceramic types (P=.065)Conclusion: Within the limitations of this study, both types of all-ceramic copings demonstrated that the mean marginal fit was considered acceptable for clinical application (≤120 μm). (Eur J Dent 2012;6:163-168)
Keywords: Marginal fit; all-ceramic types; finish lines